2011
DOI: 10.1039/c0cc05662f
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular polymeric micelles by the host–guest interaction of star-like calix[4]arene and chlorin e6 for photodynamic therapy

Abstract: A supramolecular drug delivery system has been developed via the self-assembly of a supramolecular amphiphilic polymer, which is constructed by the host-guest interaction of hydrophilic PEGylated calix[4]arene and hydrophobic photosensitizer chlorin e6. It provides a new strategy for the preparation of supramolecular polymeric micelles, and plays an important role in biological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 30 publications
0
80
0
1
Order By: Relevance
“…The incorporation of fragments able to efficiently bind inorganic ions and organic compounds into poly mers is a new strategy to designing supramolecular colloid structures and thus allows modeling of pro cesses occurring in living nature [4]. It was shown that the transition from linear to star shaped macromole cules significantly improves the capability of polymers for molecular recognition [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of fragments able to efficiently bind inorganic ions and organic compounds into poly mers is a new strategy to designing supramolecular colloid structures and thus allows modeling of pro cesses occurring in living nature [4]. It was shown that the transition from linear to star shaped macromole cules significantly improves the capability of polymers for molecular recognition [5].…”
mentioning
confidence: 99%
“…Above the LCST, the degree of hydration decreases and intramo lecular hydrogen bonds form between amide frag ments. Owing to transition to the globular conforma tion, macromolecules become hydrophobic and the polymer loses the ability to dissolve in water [3].The incorporation of fragments able to efficiently bind inorganic ions and organic compounds into poly mers is a new strategy to designing supramolecular colloid structures and thus allows modeling of pro cesses occurring in living nature [4]. It was shown that the transition from linear to star shaped macromole cules significantly improves the capability of polymers for molecular recognition [5].…”
mentioning
confidence: 99%
“…Nevertheless, unmodified CX[n] are not water soluble, and require substitution, such as the p-sulfonatocalix[n]arenes, in order to enhance their solubility for application in drug delivery [123]. Introducing hydrophilic segments, such as PEG, at the lower rims has been shown to improve the water solubility of CX[n], and the host-guest complexation of this PEGylated calixarene with a hydrophobic drug gives a supramolecular amphiphilic polymer that selfassembles into micelles [124]. The most common strategy used to prepare self-assembly systems from CX[n] is the covalent approach, whch modifies CX[n] into amphiphiles through the linkage of lipophilic groups at one rim and hydrophilic groups at the other rim.…”
Section: Receptor-mediated Endocytosismentioning
confidence: 99%
“…The tumor tissue was established by subcutaneously inoculating 5.0 10 6 MCF-7 human-breastcancer cells into the left flanks of mice. The tumors were grown to approximately 150A C H T U N G T R E N N U N G (AE30) mm 3 and a saline solution of free Ce6, Ce6-NP, or Ce6-NP-CaP that contained 2.5 mg kg À1 of Ce6 was injected into the tumor-bearing mice through the tail vein. To compare the tissue and tumor distributions of free Ce6, Ce6-NP, and Ce6-NP-CaP, mice were sacrificed after 1 day post-injection of the sample.…”
Section: In Vivo Biodistribution Of Ce6-np-capmentioning
confidence: 99%